2014
DOI: 10.25101/14.7
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Jamming: A Historical and Analytical Perspective on the Creative Process

Abstract: The process of the jazz jam session was analyzed from a historical and social perspective based on literature reviews, oral histories, interviews, and survey results. The analysis produced seven factors that facilitate the successful outcome of a jazz jam session. The factors include individual competence and knowledge of the field, practicing improvisation as the ability to overcome self-consciousness, establishing a mentoring system and role models, democracy and collaboration, leaders and sidemen, community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…In order to identify the factors and analyze the jam session model, Herzig and Baker (2014) collected data based on literature reviews, personal interviews, video analysis, and survey data. A preliminary survey conducted in 2009 with 178 participants indicated that most jazz musicians are initially attracted to the art form through recordings, live performances, and role models because of its unique process of improvisation and self-expression.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to identify the factors and analyze the jam session model, Herzig and Baker (2014) collected data based on literature reviews, personal interviews, video analysis, and survey data. A preliminary survey conducted in 2009 with 178 participants indicated that most jazz musicians are initially attracted to the art form through recordings, live performances, and role models because of its unique process of improvisation and self-expression.…”
Section: Methodsmentioning
confidence: 99%
“…The model was first proposed by Herzig and Baker (2014) within a project that documented the creative process of the jazz jam session from a historical, social, and musical perspective, and offered applications for group creativity. While there are scholars who have researched the creative process of jazz musicians and general creative thinking techniques (Cameron, 1956;Weick, 1990;Barrett, 1998;Meyer et al, 1998;Moorman and Miner, 1998;Hatch, 1998;Becker, 2000;Dennis and Macaulay, 2003;Sawyer, 1992Sawyer, , 2006Holbrook, 2008), Herzig and Baker (2014) used an in-depth historical and social perspective based on personal interviews, surveys, and a variety of historical documents to build a comprehensive model. The analysis of the jam session process revealed seven factors that facilitate group creativity and innovation.…”
Section: Development Of the Jam Session Model For Group Creativity Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Further comparisons with the jazz model are discussed in the areas of improvisational behaviors (Hatch 1998;Hatch 1999;Weick 1990;Hadida, Tarvainen, and Rose 2015), product innovation (Kamoche and Cunhae 2001;Kamoche et al 2003;Akgün et al 2007), organizational innovation (Crossan 1997;Bastien and Hostager 1998;Pasmore 1998;Holbrook 2008), actors within an organization (Kao 1996), strategic decision making (Eisenhardt 1989), market orientation (Dennis and Macaulay 2007), service performance (John, Grove, and Fisk 2006) and leadership within organizations (Walzer and Salcher 2003;Newton 2004). Herzig and Baker (2014) developed a seven-factor model for group creativity based on the jazz jam session. The seven factors are individual competence and knowledge of the field, practicing improvisation, establishing a mentoring system, democracy and collaboration, leaders and sidemen, community support, and a continuous evaluation system.…”
Section: Principles Of Creativity and Group Collaborationmentioning
confidence: 99%